CAUSES AND MECHANISMS OF PROVISION OF ECONOMIC INCENTIVES TO IMPROVE SOIL FERTILITY - Чайка, Т. О. (Scientific Progress & Innovations, 2014)
In this paper the necessity of improving soil fertility through the definition of their critical state is proved, which is associated with the development of erosive processes, increase of acidity and reduction of humus. Problem questions on designing of crop rotation are identified as an effective measure to restore soil fertility. The practice on maintenance of quality of soil and crop rotations in different EU member states is presented. The necessity of introduction of economic incentives for improvement of agro-ecological condition of farmlands is substantiated, which is based on the methods of monetary valuation of the land. The necessity of carrying out laboratory tests to determine soil quality is proved.